2014
DOI: 10.1007/s11745-014-3933-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Lipid Composition of the Copepod Limnocalanus macrurus with a High Abundance of Polyunsaturated Fatty Acids

Abstract: We studied the copepod Limnocalanus macrurus for seasonal variation in the composition of fatty acids, wax esters and sterols in large boreal lakes, where it occurs as a glacial-relict. Vast wax ester reserves of Limnocalanus were accumulated in a period of only two months, and comprised mono- and polyunsaturated fatty acids (PUFA) and saturated fatty alcohols. In winter, the mobilization of wax esters was selective, and the proportion of long-chain polyunsaturated wax esters declined first. PUFA accounted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 56 publications
3
24
1
Order By: Relevance
“…Out of all fatty acids, 16:0, 18:1(n-9), 18:2(n-6), EPA and DHA were the most abundant, together accounting approximately 56-61% of all fatty acids in June-September. In large part, our findings are in line with that of Hiltunen et al [21] who studied the fatty acid composition of L. macrurus in the Bothnian Sea in August. Similar to our study, Hiltunen et al [21] reported high proportions of these fatty acids, especially EPA and DHA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Out of all fatty acids, 16:0, 18:1(n-9), 18:2(n-6), EPA and DHA were the most abundant, together accounting approximately 56-61% of all fatty acids in June-September. In large part, our findings are in line with that of Hiltunen et al [21] who studied the fatty acid composition of L. macrurus in the Bothnian Sea in August. Similar to our study, Hiltunen et al [21] reported high proportions of these fatty acids, especially EPA and DHA.…”
Section: Discussionsupporting
confidence: 93%
“…In large part, our findings are in line with that of Hiltunen et al [21] who studied the fatty acid composition of L. macrurus in the Bothnian Sea in August. Similar to our study, Hiltunen et al [21] reported high proportions of these fatty acids, especially EPA and DHA. Conversely, in the arctic Laptev and Kara Seas, much lower proportions of PUFAs have been reported [22,23] and were probably caused by high reliance on diatoms [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our previous research (Hiltunen, Strandberg, Keinänen, Taipale, & Kankaala, 2014;Hiltunen et al, 2015) shows that these fatty acids are generally only found in L. macrurus, and not in other zooplankton taxa or seston. Our previous research (Hiltunen, Strandberg, Keinänen, Taipale, & Kankaala, 2014;Hiltunen et al, 2015) shows that these fatty acids are generally only found in L. macrurus, and not in other zooplankton taxa or seston.…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, the microbial loop can improve the quality of the C transfer pathway despite the loss of energy due to the upgrade of PUFA. For example, cladocerans are generalist filter-feeders (although they exhibit some selectivity, particularly regarding particle size; DeMott, 1982), with larger EPA contents (Hiltunen, Strandberg, Keinänen, Taipale, & Kankaala, 2014;Persson & Vrede, 2006) and faster growth and reproduction rates than copepods. For example, cladocerans are generalist filter-feeders (although they exhibit some selectivity, particularly regarding particle size; DeMott, 1982), with larger EPA contents (Hiltunen, Strandberg, Keinänen, Taipale, & Kankaala, 2014;Persson & Vrede, 2006) and faster growth and reproduction rates than copepods.…”
Section: Introductionmentioning
confidence: 99%